Akibat Hukum Pembagian Harta Warisan dalam Masyarakat Adat Karo Menurut Hukum Adat dan KUHPerdata : Studi Komparatif - Ida Nurjana Tamba; Poliman Padang; Mantasia Hasibuan; Devi Permata Br Bangun; Adelina Aritonang; Parlaungan Gabriel Siahaan; Sri Hadiningrum (Departement of Mathematics Education, 2024)
Inheritance law (erfrecht) is a set of norms or rules that regulate the transfer or transfer of rights and obligations (assets) from people who die (heirs) to people who are still alive (heirs) who have the right to receive them. Or in other words, inheritance law is a regulation that regulates the transfer of assets of a person who dies to one or several other people. Customary inheritance law is customary law which contains provisions regarding the system and principles of inheritance law, regarding the transfer of control and ownership of inherited property from the heir to the heirs. Traditional inheritance law is actually the law of passing on assets from one generation to the next. Distribution of inherited assets in the Karo traditional community, which is different from the way inheritance is distributed in law. In the Karo traditional community, the distribution of inherited assets depends on the family, so inherited assets will be passed on to the family and will not be passed on to individuals. Legal plurality. Karo custom places men and women in an unequal position. Boys as clan bearers receive honors in various traditional events, including in the process of dividing inheritance. Karo men are positioned superior to women in various sectors of life. There is a tendency for parents, both men and especially mothers, to give inheritance to their daughters in two ways, namely gift and will.